Validation of Portuguese TASIT-S in clinical populations of Autism Spectrum Disorder and Neuropsychiatric Disorders - Frazão, Patrícia Lopes (2024)
Dissertação de Mestrado em Neuropsicologia Clínica: Avaliação e Reabilitação apresentada à Faculdade de Psicologia e de Ciências da Educação